Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Based on the system of equations below, what is the value of the quotient [tex]\frac{x}{y}[/tex]?

[tex]\[
\begin{cases}
-2x + 2 = 9y - 4x \\
2x + y = -6
\end{cases}
\][/tex]

A. -7
B. -5
C. 5
D. 7


Sagot :

To solve for the quotient [tex]\(\frac{x}{y}\)[/tex] given the system of equations:

1. [tex]\[-2x + 2 = 9y - 4x\][/tex]
2. [tex]\[2x + y = -6\][/tex]

Let's first work on simplifying and solving these equations.

### Step 1: Simplify the First Equation
Starting with the first equation:
[tex]\[ -2x + 2 = 9y - 4x \][/tex]
Add [tex]\(4x\)[/tex] to both sides to get:
[tex]\[ 2x + 2 = 9y \][/tex]
Subtract 2 from both sides to isolate terms involving [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:
[tex]\[ 2x = 9y - 2 \][/tex]
We can rewrite it for simplicity:
[tex]\[ 2x - 9y = -2 \quad \text{(Equation 3)} \][/tex]

### Step 2: Simplify the Second Equation
Next, consider the second equation:
[tex]\[ 2x + y = -6 \quad \text{(Equation 2)} \][/tex]

### Step 3: Solve the System of Equations
We have the two equations:
1. [tex]\(2x - 9y = -2\)[/tex]
2. [tex]\(2x + y = -6\)[/tex]

Let's solve the system using substitution or elimination. We'll use the substitution method.

#### Isolate [tex]\(y\)[/tex] from Equation 2:
[tex]\[ 2x + y = -6 \][/tex]
Solving for [tex]\(y\)[/tex]:
[tex]\[ y = -6 - 2x \][/tex]

#### Substitute [tex]\(y\)[/tex] in Equation 3:
[tex]\[ 2x - 9(-6 - 2x) = -2 \][/tex]
Simplify within the brackets:
[tex]\[ 2x + 54 + 18x = -2 \][/tex]
Combine like terms:
[tex]\[ 20x + 54 = -2 \][/tex]
Subtract 54 from both sides:
[tex]\[ 20x = -56 \][/tex]
Divide by 20:
[tex]\[ x = -\frac{56}{20} = -\frac{14}{5} \][/tex]

#### Substitute [tex]\(x\)[/tex] back into the isolated [tex]\(y\)[/tex] equation:
[tex]\[ y = -6 - 2\left(-\frac{14}{5}\right) \][/tex]
Simplify the expression:
[tex]\[ y = -6 + \frac{28}{5} \][/tex]
To combine the terms, convert [tex]\(-6\)[/tex] to a fraction with the same denominator:
[tex]\[ -6 = \frac{-30}{5} \][/tex]
Thus:
[tex]\[ y = \frac{-30}{5} + \frac{28}{5} = \frac{-30 + 28}{5} = \frac{-2}{5} \][/tex]

### Step 4: Calculate the Quotient [tex]\(\frac{x}{y}\)[/tex]
Now that we have the values:
[tex]\[ x = -\frac{14}{5}, \quad y = -\frac{2}{5} \][/tex]
The quotient [tex]\(\frac{x}{y}\)[/tex] is:
[tex]\[ \frac{x}{y} = \frac{-\frac{14}{5}}{-\frac{2}{5}} = \frac{14}{5} \times \frac{5}{2} = \frac{14}{2} = 7 \][/tex]

### Conclusion
The value of the quotient [tex]\(\frac{x}{y}\)[/tex] is:
[tex]\[ \boxed{7} \][/tex]